Misi yang Ramah dan Estetis: Rekonstruksi Misiologi Pentakostal Melalui Perspektif Hospitalitas dan Teopoetik - Anggi Maringan Hasiholan (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. The Pentecostal mission inherited the way of colonialism in conveying the Good News to humanity. The imposition and universalisation of the doctrine to every tribe, culture, religion, and group is a common way to do it. Conversion from other religions and proselytization from other Christian sects become the achievement and measure of the mission's success. This article examines the mission's authentic meaning that can change the paradigm of conversion and proselytization as the mission's success. I used the perspective of hospitality and theopoetics to construct the authentic meaning of the Pentecostal mission. The research method used is constructive theology by Gordon Dester Kaufman. The research result showed that hospitality contributes to the courage to destroy the dividing walls of tribes, races, religions, and groups. Meanwhile, with inspiration, imagination, sensation, and beauty principles, theopoetics can provide space for little voices and encouragement to carry out social transformation.Abstrak. Misi Pentakostal mewarisi cara ekspansi agama dalam menyampaikan Kabar Baik kepada umat manusia. Pemaksaan dan universalisasi doktrin kepada setiap suku, budaya, agama, dan golongan menjadi cara yang lumrah dilakukan. Konversi dari agama lain dan proselitasi dari aliran Kristen yang lain menjadi pencapaian dan ukuran keberhasilan misi. Artikel ini bertujuan untuk mengkaji makna otentik misi yang dapat mengubah paradigma konversi dan proselitasi sebagai keberhasilan misi. Penulis menggunakan perspektif hospitalitas dan teopoetik dari Gordon Dester Kaufman untuk mengonstruksi makna otentik misi Pentakostal. Hasil penelitian menunjukkan bahwa hospitalitas berkontribusi bagi keberanian menghancurkan tembok pemisah suku, ras, agama, dan golongan. Sementara itu, dengan prinsip inspirasi, imajinasi, sensasi, dan keindahan, teopoetik mampu memberi ruang bagi suara minor dan dorongan untuk melakukan transformasi sosial.